Mencintai Produk Lokal dengan Semangat Nasionalisme Banal: Komodifikasi Memori Kebangsaan pada Iklan Merek Lokal - Fawzy, Dwimay; Rokhman, Lailiya Nur (Jurnal Komunikasi, 2024)
This article tries to explore how local brands, Indomie and Rucika, utilise commodified national memory through advertising depictions of their 50 years existence. Nationalism, which should be the basic attitude of society, is made into a commodity for business interests. Mosco’s commodification concept is used to reveal how depictions in advertising which has the potential to generate a feeling of banal nationalism. The analytical method used is Pentad analysis to interpret symbolic activity in every action and scene in advertising. The results of the analysis show that the audience's national memory is commodified through advertising by creating the perception that the two brands have accompanied the nation's journey, so consuming their products is a part of celebrating the spirit of nationalism. The depiction of the natural atmosphere and the hospitality of the people shows the characteristics of Indonesia that are highlighted in the advertisement, although in reality, this is only a small part of the reflection of reality. This has the potential to narrow our perspective on interpreting nationalism, which only revolves around “land” and “sea”.